(untitled) (Malaysian Journal of Applied Linguistics (MJoAL), 2023)
ABSTRACT One of the most significant and interesting aspects of human development is language acquisition. Since English is a universal language, it is an essential language of interaction and education. Therefore, we have to take this language of education for professional competence seriously. The aim of the study is to explore the analysis of cultural interference, an aspect that significantly hinders the learning and acquisition of English among young Malay learners. It aims to identify the students’ errors in sentence construction, particularly on the occurrence of mistakes in subject-verb-agreement’ (SVA), determiners, and the copula ‘be’. The data of this study came from an exploratory study of errors in the written essays by Year 3 students in Wangsa Maju Primary School, Malaysia. The findings of the study showed that the students were struggling and having difficulty in using accurate English grammar in their academic writing. The results revealed that the most frequent errors were the incorrect usage of the copula ‘be’ and the absence of determiners. The interference of mother tongue played a vital cause towards inhibiting the production of error free English language sentences. Lack of understanding of how the English language grammar function also accounted to this. All these could be seen as interlingual errors whereby the native language of the participants influenced their writing patterns.